Analisis usaha industri advertising di Kota Pekanbaru - Setiawan, Fery; Indrawati, Toti; Aqualo, Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Advertising industry has a good prospects when compared with the past and the present. This research is done for look at the feasibility of the advertising industry with Break Even Point analysis. This study consists of 48 advertising industry existing Pekanbaru in 2012. As for the resulting product is silk screening, billboard, banner, and advertismenrt (web line advertising). The results of the study showed that the total production which is derived from business advertising to average production amounted to Rp16.848.577,- per month. With total the amount of the production costs incurred by Rp10.638.333, so the amount of the revenue that is obtained by Rp6.210.244,- To the value of BEP unit is; silk screening 18 unit, billboard 9 unit, banner 34 unit, advertisement (web line advertising) 3 unit. And BEP rupiah is; silk screening amounted to Rp496.773,- , billboard amounted to Rp1.037.078,- , banner amounted to Rp942.439,- , and advertisement (web line advertising) amounted to Rp138.378,-. Advertising industry is expected to maintain the quality of materials and services that are already good, and has strong competitiveness to be able compete with other advertising industries.Keywords : Advertising Industry, Break Even Point, Cost, Revenue, Marketing, Labour